Manual of contract documents for highway works a user's guide and commentary : 1993/1994 amendments - Money, Bill (Thomas Telford, 1996)
This manual presents amendments to the 'Manual of Contract Documents for Highway Works: A User's Guide and Commentary'. It reintroduces national requirements in respect of Wales, Scotland and Northern Ireland, and offers clarification of some of the problematic areas.